Ultra-Deep Dolomite Reservoir Quality Classification and its Effect on Acid-Fracturing Based on Natural Fracture Activity Analysis: A Case Study of the Cambrian Subsalt Reservoir in Northern Uplift of Tarim Basin - Yin, Guoqing; Zhang, Hui; Xin, Yi; Zhang, Wei; Wu, Xingneng; Liang, Jingrui; Lai, Shujun (Frontiers in Earth Science, 2022)
Taking the >8,000 m buried Cambrian subsalt dolomite reservoir in the northern uplift of the Tarim Basin as an example, this study used imaging logging, cores, outcrops, and other data to identify natural fractures and obtain parameters of natural fractures, including strike, azimuth, width, length, and apparent porosity, and clarified the characteristics of natural fractures in the well section. Based on the logging data, wellbore rock mechanics, in situ stress, and elastic parameters were established. The analysis of the mechanical characteristics of natural fractures was carried out to find out the shear stress, normal stress, and their ratio of each natural fracture in the reservoir section. Combined with the stress value of each fracture, the quantitative characterization parameter Fractures Geomechanical Activity Index of the mechanical characteristics of natural fractures is established. Combined with the petrophysical parameters of natural fractures, the evaluation model of the quality index of the reservoir containing the natural fractures is established. According to the classification of reservoir quality, combined with the petrophysical properties of the reservoir section, the optimization of the acid-fracturing scheme and injection pressure can be carried out in order to increase the production after acid-fracturing. In this study, the quality of the reservoir with natural fractures is divided into three categories: the QRCF of a Class I reservoir is 0.6∼1, of Class II reservoir is 0.3∼0.6, and of Class III reservoir is less than 0.3. The application of Well L1 and other wells shows that there are great differences in the development of natural fractures at different depths of the Cambrian subsalt dolomite reservoir so as to QRCF. The Class I reservoir is easy for acid-fracturing to achieve high performance. The Class II reservoir needs large-scale acid-fracturing, and the Class III reservoir cannot be acid-fractured under the current methods. The research results provide a reference for the classification of the fracture mechanical activity of an ultra-deep Cambrian subsalt dolomite reservoir and the optimization of acid-fracturing treatment parameters of similar reservoirs.